The Filled Pen : Selected Non-Fiction of P.K. Page - Page, P. K. (Book collections on Project MUSE., 2006)
The essays, which cover a period of approximately forty years, reflect Page's enduring concerns as a verbal and visual artist with the power of art and the imagination to transcend the barriers that limit our perceptions of the world and our sympathies with our fellow human beings.